Diazepam-like effects of medicinal plants: A possible approach or a complementary method - Almeida-Júnior, L. D. [UNESP]; Costa, C. A.R.A. [UNESP] (My University, 2014)
Since the introduction of diazepam (DZP) by Sternbach in the 1950s, few drugs acting on GABA receptors that do not belong to the class of benzodiazepines have been introduced in therapy. DZP is one of the most prescribed drugs in clinical practice; there are many of adverse effects such as sedation, muscle relaxation, anterograde amnesia, ataxia, tolerance, dependence, benzodiazepine withdrawal syndrome, and decreased REM sleep, but these are actually desired effects in certain clinical cases and there few drugs that can serve as a substitute. In the search for new compounds, medicinal plants represent an invaluable source of substances that can act on GABA receptors and exert a diazepam-like activity, presumably with fewer side effects. Plants have been used for thousands of years to add flavor and to preserve food, to treat health disorders, and to prevent diseases. Knowledge regarding the healing properties of plants has been transmitted over the centuries among traditional communities through rituals and/or oral traditions. The data on the central nervous system activity of several plants, considered empirical, have been scientifically confirmed. Scientists continue to discover new drugs and new uses for older drugs with improved quality and safety, but some of these products are not commercialized. There is an impressive array of natural products that influence the function of GABAergic receptors. Substances or products derived from medicinal plants may have activity through these receptors. In this chapter, the diazepam-like properties of medicinal are reviewed. A discussion about the possibility of using medicinal plants as a substitute for DZP and their complementary use in an approach that seeks a synergistic effect between the chemical constituents obtained from the different plant species and from the standard drug DZP, is approached to determine if the use of these plants is a possible approach or a complementary therapy with DZP. The complexity of the interactions between the active constituents of herbal preparations are important for the final effect, and such compounds may potentiate the effects of standard drugs. One mechanism does not exclude the other. Finally, we found a number of potential natural products that can serve as a prototype for the production of new medicines and are good candidates for further investigation that could eventually result in clinical use.
Keywords: Central nervous system; Complementary therapy; Diazepam-like activity; GABA; Medicinal plants; Synergism